Response to the letter: 'Comments on misinterpretation of the proton nuclear magnetic resonance spectroscopic data of a previous study' by Orhan&Irmak - Arslan, H.; Karatas, E.; Keskin, A. (Wiley, 2020)
[Abstract Not Available]
Keywords: Sodium-Hypochlorite; Para-Chloroaniline; Chlorhexidine; Mixture